Endosomal trafficking defects in patient cells with KIAA1109 biallelic variants - Megan S. Kane; Callie J. Diamonstein; Natalie Hauser; John F. Deeken; John E. Niederhuber; Thierry Vilboux (Genes and Diseases, 2019)
The uncharacterized gene KIAA1109 has recently been associated with a congenital neurological malformation disorder that variably presents with arthrogryposis, craniofacial and/or cardiac abnormalities. We have identified two additional patients with compound heterozygous KIAA1109 variants presenting with the same neurological malformations. The mechanism whereby KIAA1109 loss of function causes this spectrum of disorders was the primary focus of our studies. We hypothesized that KIAA1109 function could be conserved relative to the fly gene tweek and examined endocytosis and endosome recycling in patient fibroblasts. Furthermore, we examined the structure of the cytoskeleton and cilia based on functional overlap with endocytosis and several known etiologies for neuronal migration disorders. Utilizing primary dermal fibroblasts from one patient and a healthy donor, we performed immunofluorescence and endocytosis assays to examine the endosomal, cytoskeletal, and ciliary cellular phenotypes. We found notable abnormalities in endosomal trafficking and endosome recycling pathways. We also observed changes in the actin cytoskeleton and cilia structural dynamics. We conclude that the function of KIAA1109 in humans may indeed overlap with the function of the Drosophila ortholog, resulting in perturbations to endosomal trafficking and the actin cytoskeleton. These alterations have ripple effects, altering many pathways that are critical for proper neuronal migration and embryonic development. Keywords: Cilia, Endocytosis, KIAA1109, Neurological malformation, Vesicular trafficking